2018
DOI: 10.1177/000313481808400729
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 334 Cases of Pediatric Esophageal Foreign Body Removal Suggests that Traditional Methods Have Similar Outcomes Whereas a Magnetic Tip Orogastric Tube Appears to be an Effective, Efficient, and Safe Technique for Disc Battery Removal

Abstract: Procedures and outcomes for pediatric esophageal foreign body removal were analyzed. Traditional methods of battery removal were compared with a magnetic tip orogastric tube (MtOGT). A single institution retrospective review from 1997 to 2014 of pediatric patients with esophageal foreign bodies was performed. Balloon extraction with fluoroscopy (performed in 173 patients with 91% success), flexible endoscopy (92% success in 102 patients), and rigid esophagoscopy (95% in 38 patients) had excellent success rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…Concerns that have been raised include the inability to inspect the esophageal mucosa after removal, the possibility of missing other ingested objects that are not radio-opaque, lack of airway protection during the procedure, radiation exposure, and discomfort of the patient. 15 16 17 However, this study and other articles have shown that both fluoroscopy time, with a mean time between 2 and 2.5 minutes, and complication rates, with 10 or fewer complications reported in each study, are low. 5 8 No patients in our population returned to the ER due to persistent symptoms related to an undiagnosed, retained second radiolucent foreign body.…”
Section: Discussioncontrasting
confidence: 57%
“…Concerns that have been raised include the inability to inspect the esophageal mucosa after removal, the possibility of missing other ingested objects that are not radio-opaque, lack of airway protection during the procedure, radiation exposure, and discomfort of the patient. 15 16 17 However, this study and other articles have shown that both fluoroscopy time, with a mean time between 2 and 2.5 minutes, and complication rates, with 10 or fewer complications reported in each study, are low. 5 8 No patients in our population returned to the ER due to persistent symptoms related to an undiagnosed, retained second radiolucent foreign body.…”
Section: Discussioncontrasting
confidence: 57%
“…For the retrieval methods, the oral-gastric tube with a magnetic tip under fluoroscopy and rigid esophageal endoscopy technique have the highest success rates [ 7 ], but each method has its own risks to consider. Rigid esophageal endoscopy may slightly increase the perforation rate [ 8 ], although the difference has not been shown to be significant in children [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A magnet-tipped orogastric tube was observed to be the most rapid method for disk battery removal, associated with a high success rate compared with balloon extraction, flexible endoscopy, and rigid esophagoscopy [ 38 ].…”
Section: Advantage Over Endoscopic Removalmentioning
confidence: 99%